The Effect of Trichoderma and Bokashi Fertilizer Production and Intensity of Dowdy Death (Peronosclerospora maydis) on Sweet Corn (Zea mays sacharata Sturt) Plants - Lahati, Betty Kadir; Sabban, Helda (Agrikan Jurnal Agribisnis Perikanan, 2023)
This research aims to test the effect of Trichoderma and Bokashi biological fertilizers on the intensity of downy mildew and production of corn (Zea mays sp.). The research method uses an experimental method by testing Trichoshi fertilizer, namely a combination of Trichoderma harzianum species and Bokashi biological fertilizer made from goat manure using a Randomized Design. Group (RAK) consisting of 4 treatments and 3 replications. The Trichoshi fertilizer treatment consisted of A=without Trichoshi 0.00 g/m², B=Trichoshi 150 g/m², C=Trichoshi 200g/m² and D=Trichoshi 250 g/m². The observation parameters consist of production and intensity of downy mildew on sweet corn. Data analysis used analysis of variance (ANOVA) at a significance level of 5%. If there is a significant difference between treatments, a Duncan test at 5% level is carried out. The output of the research will be published in the National journal Sinta 4. Technology Readiness Level, namely TKT 3. Based on the results of statistical analysis, it shows that the effect of Trichoderma and Bokashi (Trichoshi) fertilizers on the growth and yield of corn production has a good effect on corn production reaching 6.27 tons/ha compared to other crops. corn that was not given Trichoshi fertilizer only reached 2.65 tonnes/ha. Apart from that, giving Trichoshi to corn plants can reduce the intensity of downy mildew attacks by up to 0.03% compared to corn plants that are not given Trichoshi fertilizer, the attack intensity reaches 1.27%. The intensity category of downy mildew attacks on corn plants is on the light category scale.